2016
DOI: 10.1002/jmrs.162
|View full text |Cite
|
Sign up to set email alerts
|

Use of a prospective cohort study in the development of a bladder scanning protocol to assist in bladder filling consistency for prostate cancer patients receiving radiation therapy

Abstract: IntroductionEvidence of variations in bladder filling effecting prostate stability and therefore treatment and side‐effects is well established with intensity modulated radiation therapy (IMRT). This study aimed to increase bladder volume reproducibility for prostate radiation therapy by implementing a bladder scanning (BS) protocol that could assist patients' bladder filling at computed tomography (CT) simulation and treatment.MethodsBased on a retrospective review of 524 prostate cancer patients, a bladder v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 7 publications
(16 reference statements)
0
27
0
2
Order By: Relevance
“…Generally, when calculating the distribution probability, the normal or near-normal distribution data can be used (mean ± 2SD) to specify the probability range [14]. There have been different understandings and de nitions of the consistency of BV, but they have not proved whether it is suitable for most patients with pelvic cancer [8,11]. Judgment consistency cannot blindly expand the reference range, it should be judged according to the actual situation of the patient.…”
Section: Consistency Judgment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, when calculating the distribution probability, the normal or near-normal distribution data can be used (mean ± 2SD) to specify the probability range [14]. There have been different understandings and de nitions of the consistency of BV, but they have not proved whether it is suitable for most patients with pelvic cancer [8,11]. Judgment consistency cannot blindly expand the reference range, it should be judged according to the actual situation of the patient.…”
Section: Consistency Judgment Methodsmentioning
confidence: 99%
“…Fujioka et al believed that the mean relative bladder volume (RBV) was at least 70%, and based on the results of the mean values of BV receiving more than 70 Gy(V 70Gy ) and 50 Gy(V 50Gy ) in each subgroup, the cutoff value (mean + 2standard deviations [SD]) at the upper bounds of the 95% con dence interval was determined [8]. Cramp et al believed that the BV was reasonable when it was 250-350 mL, and the RBV > 50% was considered to be up to standard [11]. Hong In Yoon et al thought that when the bladder volume of patients ranged from 80-120% of that of the simulation CT scan, patients were instructed to keep the same pattern of bladder lling the following day [12].…”
Section: Introductionmentioning
confidence: 99%
“…Their study underlined the importance of more objective bladder filling protocols and using an ultrasound bladder scanner as a screening tool to identify patients with large bladder filling variations during treatment. More recently, Cramp et al (2015) conducted a feasibility study that used an ultrasound bladder scanner before CT simulation and compared it with a retrospective study of 524 bladder volumes analyzed from prostate planning [25]. Patients were planned when they demonstrated a 250-350 mL bladder volume, which was adopted as being ''ideal'' for achieving planning dose constraints.…”
Section: Discussionmentioning
confidence: 99%
“…This could be especially useful for treatments requiring a high degree of conformality such as SABR or boosting of dominant intra-prostatic lesions. A retrospective study of electromagnetic transponders in 236 patients undergoing prostate radiotherapy observed that changes in intra-fractional prostate position were more likely the longer the treatment delivery time [38]. Variations of >3 mm were seen for 12 % of the time taken to deliver fixed-field IMRT delivered within 10 minutes, compared to only 4 % for more rapidly-delivered volumetric modulated arc therapy (VMAT) treatments completed within 5 minutes.…”
Section: Electromagnetic Transpondersmentioning
confidence: 99%